2019
DOI: 10.1055/s-0039-3400457
|View full text |Cite
|
Sign up to set email alerts
|

Association of Menopausal Status, Expression of Progesterone Receptor and Ki67 to the Clinical Response to Neoadjuvant Chemotherapy in Luminal Breast Cancer

Abstract: Objective To identify the biomarkers of response to neoadjuvant chemotherapy in early luminal breast cancer. Methods A cross-sectional study that included all patients with early or locally-advanced luminal breast cancer submitted to neoadjuvant chemotherapy between 2013 and 2014. Demographic, clinic and pathologic data were retrieved from patient records. The expressions of the estrogen receptor (ER), the progesterone receptor (PR), and Ki67 were analyzed by immunohistochemistry (IHC). The status of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
8
1
Order By: Relevance
“…In the study of Silva et al 23 , it was shown that patients with high Ki-67 proliferation index had a better response to neoadjuvant chemotherapy and had a higher rate of clinical complete response. In this study, the cut-off value for Ki-67 was taken as 14% (p=0.005).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the study of Silva et al 23 , it was shown that patients with high Ki-67 proliferation index had a better response to neoadjuvant chemotherapy and had a higher rate of clinical complete response. In this study, the cut-off value for Ki-67 was taken as 14% (p=0.005).…”
Section: Discussionmentioning
confidence: 98%
“…Breast cancer is the most common cancer seen in women. According to Globocan 2020, 23.9% of cancers seen in women in our country are breast cancer. Breast cancer is the second most common cause of cancer mortality in our country and in the USA 1,2 .…”
Section: Introductionmentioning
confidence: 99%
“…According to this study, DFS of patients with BC decreased gradually when Ki-67 index value increased from 50% to 58%, but the interval of Ki-67 index to judgment of DFS was relatively small and special attentions shall be paid to it. However, some study show that when the critical value of Ki-67 index was determined 14%, patients with Luminal-type BC and high Ki-67 expression (≥14%) and low PR expression (<50%) achieved a relatively high clinical complete remission (CR) from neoadjuvant chemotherapy [21].…”
Section: Discussionmentioning
confidence: 99%
“…Deriese and Crabtree 30 et al studied the relationship between Ki67 and renal cancer tissues and found that the degree of tumor grade was positively correlated with the expression of Ki67-positive cells, and the proliferation index of Ki67 was closely related to the prognosis of renal cancer. In addition, there is a large amount of literature showing that Ki67 is related to breast cancer 31 33 , rectal cancer 34 , and pancreatic neuroendocrine tumor 35 .…”
Section: Discussionmentioning
confidence: 99%